2019
DOI: 10.1042/bsr20190170
|View full text |Cite|
|
Sign up to set email alerts
|

Osteogenic protein-1 alleviates high glucose microenvironment-caused degenerative changes in nucleus pulposus cells

Abstract: Increasing evidence has indicated a close relationship between diabetes mellitus (DM) and disc degeneration. As a potential therapeutic growth factor, osteogenic protein-1 (OP-1) has lots of protective effects on the healthy disc cell’s biology. The present study was aimed to investigate the effects of OP-1 on degenerative changes of nucleus pulposus (NP) cells in a high glucose culture. Rat NP cells were cultured in the baseline medium or the high glucose (0.2 M) culture medium. OP-1 was added into the high g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Because normal AF cell viability is responsible for maintaining of the ECM in AF tissue, inhibiting high glucose-induced AF cell apoptosis may be a potential way to retard disc degeneration in DM patients. In line with us, several previous studies have shown that high glucose significantly affected biological behaviors of intervertebral disc cells, such as promoting cell apoptosis [15,19], accelerating autophagy [37], decreasing matrix biosynthesis [14] and inducing cellular senescence [15,38]. Together, these studies indicate that a high glucose environment is harmful to the healthy cellular activities of disc cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Because normal AF cell viability is responsible for maintaining of the ECM in AF tissue, inhibiting high glucose-induced AF cell apoptosis may be a potential way to retard disc degeneration in DM patients. In line with us, several previous studies have shown that high glucose significantly affected biological behaviors of intervertebral disc cells, such as promoting cell apoptosis [15,19], accelerating autophagy [37], decreasing matrix biosynthesis [14] and inducing cellular senescence [15,38]. Together, these studies indicate that a high glucose environment is harmful to the healthy cellular activities of disc cells.…”
Section: Discussionsupporting
confidence: 83%
“…DM often induces many complications including cardiovascular issue, renal failure and neuropathy [9]. Several studies have reported that DM is a potential etiological factor of intervertebral disc degeneration [10][11][12][13][14][15]. Moreover, some researchers have demonstrated that high glucose can promote apoptosis of disc cartilage endplate cells and notochordal cells, and ultimately accelerate the progression of disc degeneration [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of DM (type 1 DM and type 2 DM) with approximately 90% of DM patients are type 2 DM [1]. Accumulating evidence has shown that DM is a crucial effecter in the progression of intervertebral disc degeneration [2][3][4][5][6]. The morbidity of disc degeneration is much higher in DM patients than that in non-DM patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies demonstrated that diabetes mellitus (DM) is a risk factor of IDD in a DM patient, and DM patients have a higher incidence and a faster progress of IDD than non-DM patients [2][3][4][5]. Furthermore, several basic researches reported that DM-associated hyperglycemia is harmful to the health biology of disc cells [6][7][8][9][10][11][12][13][14]. Currently, many researchers have managed to investigate the pathogenesis of IDD in DM patients.…”
Section: Introductionmentioning
confidence: 99%